Hubungan Pengetahuan Ibu tentang Imunisasi dan Kelengkapan Imunisasi Dasar dengan Kejadian Stunting pada Batita di Wilayah Kerja Puskesmas Baiturrahman - Ananda, Ameliya; Nevi Hasrati Nizami; Sri Agustina (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Stunting is a term from a dwarf or short body in children under the age of 5 years that experiences a condition of failure to grow due to chronic malnutrition and recurring infections that occur during the period of the first 1,000 days of life (HPK), namely from the fetus to children aged 24 months. This study aims to determine the relationship between mother's knowledge about immunization and the completeness of basic immunization with the incidence of stunting in toddlers in the working area of the Baiturrahman Health Center. This type of research is quantitative descriptive correlative. The population of all mothers who have toddlers in the working area of the Baiturrahman Health Center in Banda Aceh City, with a total population of 584 toddlers. The sampling technique uses purposive sampling so as to obtain the number of samples of 85 respondents. Data collection techniques using a modified questionnaire from previous studies with the R count validity test (0.968) and the validity test results (0.936) and observation sheets. The results showed that the mother's knowledge of immunization was in the good category (72.9%), the majority of stunting (57.6%), with a complete basic immunization status (89.4%). The absence of a significant relationship between mother's knowledge of immunization and the incidence of stunting p-value 0.120 (> 0.05). There is a significant relationship between the status of a decades of immunization and the event of stunting, with a p-value of 0.023 (<0.05).